2021
DOI: 10.1016/j.ijid.2020.11.142
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of favipiravir, an oral RNA-dependent RNA polymerase inhibitor, in mild-to-moderate COVID-19: A randomized, comparative, open-label, multicenter, phase 3 clinical trial

Abstract: Highlights Favipiravir is an oral RNA-dependent RNA polymerase inhibitor. Favipiravir is under investigation in many countries for treatment of COVID-19. We evaluated favipiravir’s efficacy and safety in mild-to-moderate COVID-19. Favipiravir treatment led to significant improvement in time to clinical cure. Favipiravir may be a safe and effective treatment in mild-to-moderate COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
250
2
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(269 citation statements)
references
References 26 publications
7
250
2
10
Order By: Relevance
“…To assess the efficacy and safety of favipiravir in adults with mild-to-moderate coronavirus disease, Udwadia et al [ 28 ] conducted a randomized, comparative, open-labeled, phase 3 clinical trial. This study included 150 adults (18–75 years) with RT-PCR confirmed COVID-19 and mild-to-moderate symptoms (including asymptomatic) ( Table 1 ), plus standard supportive care ( n = 75) versus supportive care alone ( n = 75).…”
Section: Sars-cov-2 Infectionmentioning
confidence: 99%
“…To assess the efficacy and safety of favipiravir in adults with mild-to-moderate coronavirus disease, Udwadia et al [ 28 ] conducted a randomized, comparative, open-labeled, phase 3 clinical trial. This study included 150 adults (18–75 years) with RT-PCR confirmed COVID-19 and mild-to-moderate symptoms (including asymptomatic) ( Table 1 ), plus standard supportive care ( n = 75) versus supportive care alone ( n = 75).…”
Section: Sars-cov-2 Infectionmentioning
confidence: 99%
“…conducted in China 3 , 4 , 6 and one each in Russia 2 and Oman. 5 The comparator varied, including lopinavir/ritonavir, 3 umifenovir, 6 hydroxychloroquine, 5 baloxavir 4 and standard of care. 2 , 4 First, the pooled analysis of five studies [2][3][4][5][6] showed that favipiravir was associated with a higher clinical improvement rate than control group, but the difference did not reach statistical significance (odds ratio [OR], 1.54; 95% CI, 0.78-3.04; I 2 = 43%, Fig.…”
mentioning
confidence: 99%
“… [1] However, the efficacy of favipiravir for treating COVID-19 remained unclear and was not assessed in this study. In fact, several clinical studies [2] , [3] , [4] , [5] , [6] investigating the usefulness of favipiravir for COVID-19 patients have been published and provides us the opportunity to re- assess the clinical efficacy and safety of favipiravir. Therefore, we did a meta-analysis of these clinical studies to provide an update data to clarify this issue –the clinical efficacy and safety of favipiravir in the treatment of COVID-19 patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations